The Implementation of Problem Based Learning Models to Improve Understanding of Fantasy Story Texts - Wita Dwi Payana; Lismalinda Lismalinda (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
Numerous pupils are still unable to convey their thoughts and ideas in order to think more critically about an issue. As a result, individuals require another method of learning for the purpose of enhancing their capabilities. Problem Based Learning is a learning style in which students are required to solve real-world situations. Using a problem-based learning method, this study aims to explain the increasing in students' understanding of fantasy story texts. The study population consisted of 29 students from class VII Bilingual B SMP Al-Azhar Medan. The examination was carried out randomly using a random sampling inspection procedure. This study adopted a quasi-experimental design with one-group pretest and one-group posttest. The pretest is carried out before the problem-based learning model is applied. The results of the pretest will be evaluated as a benchmark for building values and developing arrangements through problem-based learning. The post-test is given after the learning has been completed. The assignment-based written test serves as research instruments. The data was assessed by describing the pre and post test results. The results showed that students achieved an average score of 90.79% in the complete KKM 88 category after using a problem-based learning model with fantasy story text.